ENHANCING ELEMENTARY EFL LEARNERS’ UNDERSTANDING OF TIME EXPRESSIONS THROUGH INTERACTIVE WORKSHEETS - Novelia Fitriani; Angelia Margono; Masda Egy Faradilla; Siti Hamidah; Abdul Syahid; Heny Suriandari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Understanding time concepts and their linguistic expressions remains a significant challenge for elementary EFL learners due to the lack of engaging and contextual learning materials. This Classroom Action Research aimed to enhance Grade III students’ mastery of